Penerapan Teknik Self management untuk Meningkatkan Gaya Kepemimpinan - Kurniawan, Andi (Program Studi Bimbingan dan Konseling Islam, 2023)
The purpose of this research is to test self management techniques to improve the leadership style of Ranting Ansor Gintangan. This type of research is a case study, the method used in this research is qualitative. The data collection techniques used in this research used participant observation, in-depth interviews, and documentation. Based on the results of observations and interviews, self management techniques can influence individual development in the aspects of motivation, communication, actions, thoughts, hard work, time management, and spirituality. In general, each individual has self management. The subjects in this study used 1 main subject and 2 supporting informants. The results of the research showed that the leadership style used before self management techniques intervened was that the leader had to be seen. In the last 3 months, based on the results of interviews and observations, it shows that there have been changes and improvements in Ansor Gintangan's leadership after implementing self management techniques. The behavioral changes that emerge are as follows; subjects communicate more frequently in two directions so that members feel that democracy within the organization is running, the more active discussions are in the WhatsApp media group as a means to grow trust, the more they understand the condition of their members. So that the running of the organization becomes smooth and effective.